USE OF LIBRARIES AND INFORMATION CENTRES BY SCIENTISTS AND TECHNOLOGISTS IN BANGLADESH - Rahman, Md. Mostafizur; Binwal, J.C. (Malaysian Journal of Library and Information Science, 2000)
Scientists and technologists are major users of libraries and information centres. This paper studies their usage pattern by considering the influence of their background variables, namely, age, gender, qualifications and status. The study sample population consists of 246 scientists and technologists from two major scientific and technical research institutes in Bangladesh. One-way analysis of variance (ANOVA) statistical test was used to test the hypotheses and the results of the analysis show that the socio-economic background variables influence the use of libraries and information centres.